Psychopathic Personality Traits and the Risk for Personal Victimization - Boccio, Cashen M. (Journal of interpersonal violence, 2021)
Previous research links psychopathic traits with involvement in criminal behavior and numerous negative life outcomes. To date, however, a relatively limited amount of research has examined whether psychopathic traits confer an increased risk of victimization. This area of research is of interest as some scholars contend that psychopathic traits may confer several advantages for life outcomes including outcomes related to criminal conduct. As a result, psychopaths may be at a decreased risk of victimization. On the contrary, research examining the victim–offender overlap indicates that as psychopaths are likely to be involved in criminal behavior they would be more likely to be victimized. This article addresses this gap in the literature by examining whether psychopathic personality traits are associated with odds of victimization in a large nationally representative sample of Americans from adolescence to adulthood. Specifically, our study employs logistic regression and Poisson regression to test associations between psychopathic personality traits and victimization in data drawn from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Our findings reveal that psychopathic personality traits are positively associated with odds of victimization in adolescence and adulthood. In addition, our findings indicate that psychopathic personality traits interact with criminal involvement to predict odds of victimization. The findings of our study have implications for the literatures concerning successful psychopathy and the victim–offender overlap.